Products for conscious consumers : developing, marketing and selling ethical products - Ogunyemi, Kemi; Burgal, Vanessa (Emerald Publishing Limited, 2022)
Consumers are becoming more conscious of the ethical footprint of the products they buy. In the age of hyper-connectivity and globalisation, numerous consumers are aware of what companies do and how they produce. Thus, sustainability and CSR can no longer be used as "greenwashing" strategies to attract customers and improve a company image. Products for Conscious Consumers is a guide for academics, students and professionals who want to influence responsible consumer behaviour and attain genuine Green Marketing. Written by researchers and marketing professionals, each chapter explores the relationship between the consumer and the marketer, discussing their relative responsibilities towards reaching a sustainable world. Illustrated with real cases, Products for Conscious Consumers helps marketers understand how they can inspire consumers towards more ethical behaviour by educating and nudging their choices using examples from different sectors and world regions to identify factors that influence sustainable consumption, from poverty to personal values. Products for Conscious Consumers guides the reader from ethical product development and marketing plans to eco-friendly production and responsible marketing mix execution, thereby encouraging a sustainable value chain and ethical profitability.